2011
DOI: 10.1038/onc.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

The balance between rRNA and ribosomal protein synthesis up- and downregulates the tumour suppressor p53 in mammalian cells

Abstract: Data on the relationship between ribosome biogenesis and p53 function indicate that the tumour suppressor can be activated by either nucleolar disruption or ribosomal protein defects. However, there is increasing evidence that the induction of p53 does not always require these severe cellular changes, and data are still lacking on a possible role of ribosome biogenesis in the downregulation of p53. Here, we studied the effect of the up-and downregulation of the rRNA transcription rate on p53 induction in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 66 publications
7
94
0
Order By: Relevance
“…The altered expression of RPL11 and RPL5 in response to treatment with both AKTi-1/2 (decreased) and CX-5461 (increased) is also consistent with a previous report suggesting the importance of an imbalance between rRNA and RP synthesis for the activation of p53 in response to the disruption of rDNA transcription (40). Specifically, the presence of free RPs in excess of rRNA, as a consequence of the selective inhibition of rDNA transcription, is intrinsic to the induction of p53 by CX-5461, whereas the concomitant decrease in the synthesis of RPs and rRNA following Fig.…”
Section: Research Briefsupporting
confidence: 76%
See 1 more Smart Citation
“…The altered expression of RPL11 and RPL5 in response to treatment with both AKTi-1/2 (decreased) and CX-5461 (increased) is also consistent with a previous report suggesting the importance of an imbalance between rRNA and RP synthesis for the activation of p53 in response to the disruption of rDNA transcription (40). Specifically, the presence of free RPs in excess of rRNA, as a consequence of the selective inhibition of rDNA transcription, is intrinsic to the induction of p53 by CX-5461, whereas the concomitant decrease in the synthesis of RPs and rRNA following Fig.…”
Section: Research Briefsupporting
confidence: 76%
“…In contrast, PI3K-AKT-mTOR inhibitor-mediated suppression of rDNA transcription rates occurred in the absence of nucleolar disruption and p53 pathway activation and was instead associated with the upregulation of BMF protein. The lack of p53 stabilization following selective inhibition of mTORC1 signaling by rapamycin has been previously reported (40,41); however, the mechanism underpinning the absence of a nucleolar stress response despite disruption of ribosome biogenesis remained undefined. Here, we demonstrate that the absence of p53 activation following AKT-mTORC1 inhibition, despite the robust reduction of rDNA transcription rates, was associated with decreased proportions of ribosomes in translationally active polysomes, and reduced abundance of critical nucleolar stress-related RPs (RPL11 and RPL5).…”
Section: Research Briefmentioning
confidence: 99%
“…S1). Moreover, in a recent study, we observed that POLR1A siRNA did not induce variations in ribosomal protein L5 and L11 synthesis 48 hours after the end of the silencing procedure (Donati et al, 2011). The early inhibition of protein synthesis observed by Fumagalli and colleagues (Fumagalli et al, 2009) might be due to the specific approach to hinder ribosome biogenesis.…”
Section: Polr1a Silencing Downregulates the Synthesis Of Rrnamentioning
confidence: 99%
“…This inhibition results in the relocalisation of many RPs (L11, L5, L23, S7 and S3) from the nucleolus to the nucleoplasm, triggering their interaction with Mdm2. There is also evidence that decrease in rRNA levels alone in the absence of nucleolar disruption results in excess of RPs that are sufficient to promote binding of RPs to Mdm2 (Donati et al, 2011). The binding of RPs to Mdm2 inhibits Mdm2 activity to degrade p53, leading to p53 stabilisation and p53-dependent cell cycle arrest (Lindstrom, 2009;Zhang and Lu, 2009).…”
Section: Introductionmentioning
confidence: 99%